PENYUSUNAN PERENCANAAN PROGRAM KERJA UNTUK PENINGKATKAN MUTU LULUSAN - Mutrofiah Mutrofiah (UNIVERSITAS BENGKULU, 2015)
The aimed of the research was to describe the arraying of school planing program to improving the graduated quality in State Senior High School 2 Muara Beliti Musi Rawasregency.The method of research using descriptive qualitative. The subject of the research were school commitee, principal, vice principal, and teachers. Tehnique of collecting the data wereobservation, interview and documentation. The result of the research were: first, the arranging of program, second, the decrement of vision and mision and the purpose of the school. Third, the result of the planning applied on the all of school activities. The last, supervision of the planning was done throught supervision, evaluation that can be seen on student achievement.Keyword: planning, programming, quality of graduates